قلع الأسنان عند المرضى الخاضعين للعلاج بالوارفارين (دراسة مستقبلية وصفية) (Latakia University Journal -Medical Sciences Series, 2012)
دراسة مستقبلية وصفية تمت على 32 مريضاً من مراجعي قسم جراحة الفم والفكين- جامعة تشرين ممن لديهم أمراض قلبية ووعائية مختلفة والخاضعين للعلاج بمميعات الدم(الوارفارين) حيث هدفت الدراسة إلى تحديد قيم INR  التي تجعل بالإمكان إجراء قلوع الأسنان لدى هؤلاء المرضى دون إيقاف أو تعديل في جرعات مميعات الدم وبدون تعريض المرضى لخطورة العمل الجراحي ولإتمام هذه الدراسة قمنا باستخدام المتغيرات التالية: نوع العلاج الجراحي, طبيعة الإصابة القلبية, جرعة مميعات الدم, قيم INR, الطرق المستخدمة في الإرقاء الموضعي. خضع 56.25 % من المرضى لقلوع أسنان مفردة, 25% قلوع متعددة, 18.75% قلوع جراحية وكان القيم الوسطى لل INR 2.38 بتفاوت طبيعي قدره 0.07 وبمعدل التشتت 0.27 وهذا يعني أنه ذو دلالة ضعيفة وبفضل الطرق المستخدمة في الإرقاء الموضعي لم يحدث أي اختلاط نزفي ما بعد العمل الجراحي لذلك بدا لنا بالنتيجة بأن خطورة حدوث حوادث صمات خثرية ناجمة عن وقف مميعات الدم هي أكثر خطورة على حياة المريض من احتمال النزوف في حال عدم إيقافها.The study is prospective and descriptive. It take place in the department of oral surgery in Tishreen university. It concerned 32 patients presented a cardiovascular pathology, having required an warfarine therapy, and also need an act of oral surgery. The objective of this study was to determine the INR value making possible to carry out an act of oral surgery without haemorrhagic risk. We exploited the following parameters: identification of the patient, oral state, type of oral surgery, type of cardiopathy, AVK posology, INR value, means haemostasis. 56.25% of our patients had undergone a single extraction, 25% had beneficed multiple extractions, and 18.75% had profited from surgical extraction. The average value of the INR was 2.38 with an variance of 0.07 and an ecart type of 0.27. In favour of the haemostat means, no haemorrhagic complication post operational was revealed. It is allowed that the risk of thromboembolic accident by stoping the treatment is much more prejudicial than hemorrhagic risk for the patent.